Efektivitas Komunikasi Interpersonal Dalam Menjalin Solidaritas Virtual Melalui Aplikasi Steam Community Grup - Laksono, Tri Agung; Oxcygentry, Oky; Arindawati, Weni A. (CV. ITTC INDONESIA, 2024)
To communicate and interact with each other while in an online game, the Steam Community application is an application that can be used to interact and communicate with Steam Community users, and also has the feature of creating a group, one of which is the GabutGaming group. In a Steam Community GabutGaming Group, interaction and communication are required to be connected to an internet connection and there are also different variations of members such as regional differences, age, language and culture. This study aims to determine the effectiveness of using the Steam Community application in establishing virtual solidarity in the GabutGaming Group. This research uses a Qualitative research method with a Case Study approach and then uses interviews and data collection. Researchers have obtained the results of research from the existence of Openness, Empathy, Supportive Attitudes, Positive Attitudes and Equality. Where from the five positive traits, communication can run effectively to increase the sense of solidarity that occurs virtually in a Steam Community application for the GabutGaming group.